2009
DOI: 10.1002/ejoc.200900823
|View full text |Cite
|
Sign up to set email alerts
|

Drastic Solid‐State Fluorescence Enhancement Behaviour of Phenanthro[9,10‐d]imidazole‐Type Fluorescent Hosts upon Inclusion of Carboxylic Acids

Abstract: The crystals of phenanthro[9,10‐d]imidazole‐type fluorescent host 1 exhibit drastic fluorescence enhancement behaviour with a redshift in the emission maximum upon enclathration of various carboxylic acids such as formic acid, acetic acid and propionic acid. The optical changes are greatly dependent on the identity of the enclathrated carboxylic acids. The fluorescent clathrate compounds are formed not only by cocrystallization from carboxylic acid solutions but also by solid (fluorescent host)–gas (carboxylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, recent works highlighted the interest of simple and small molecular weight D-π-A push-pull dipolar fluorophores, in which an electron donating group D is connected to an electron-withdrawing group A via a π-conjugated bridge, for the design of efficient solid-state emitters. [22][23][24][25][26][27] , [28][29][30][31] , [32][33][34][35][36][37][38][39] , [40] , [41] The permanent dipole moment associated with the D-π-A structure gives rise to strong dipole-dipole interactions that can induce specific organization and orientation of molecules in the solid-state and favors the formation of emissive aggregates. Moreover, since the fluorescence of such dipolar fluorophores is usually characterized by a large Stokes shift, red and even far-red emission wavelengths over 700 nm are accessible, providing appropriate combinations of electron-donor and acceptor groups.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent works highlighted the interest of simple and small molecular weight D-π-A push-pull dipolar fluorophores, in which an electron donating group D is connected to an electron-withdrawing group A via a π-conjugated bridge, for the design of efficient solid-state emitters. [22][23][24][25][26][27] , [28][29][30][31] , [32][33][34][35][36][37][38][39] , [40] , [41] The permanent dipole moment associated with the D-π-A structure gives rise to strong dipole-dipole interactions that can induce specific organization and orientation of molecules in the solid-state and favors the formation of emissive aggregates. Moreover, since the fluorescence of such dipolar fluorophores is usually characterized by a large Stokes shift, red and even far-red emission wavelengths over 700 nm are accessible, providing appropriate combinations of electron-donor and acceptor groups.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state fluorescent organic compounds have been widely investigated owing to their broad application potential in different fields. One such material features an organic fluorescent host, which can exhibit fluorescence enhancement with a blue-shift emission upon the inclusion of solvent molecules, associated with CH−π and π–π interactions and modification to the intermolecular hydrogen bonds. Ooyama et al reported that crystals of phenanthro­[9,10- d ]­imidazole P60 (Scheme ), a fluorescent host, exhibited sharp emission enhancement with a red-shift in the emission maximum upon the enclathration of carboxylic acids such as formic acid, acetic acid, and propionic acid . The resulting fluorescent clathrate structure was formed by the cocrystallization of carboxylic acid solutions and by solid (fluorescent host)–gas (carboxylic acid vapor) contact, as described by the authors.…”
Section: Dual-functional Fluorescent/colorimetric Sensors Based On Ph...mentioning
confidence: 99%
“…175−178 Ooyama et al reported that crystals of phenanthro [9,10d]imidazole P60 (Scheme 8), a fluorescent host, exhibited sharp emission enhancement with a red-shift in the emission maximum upon the enclathration of carboxylic acids such as formic acid, acetic acid, and propionic acid. 179 The resulting fluorescent clathrate structure was formed by the cocrystallization of carboxylic acid solutions and by solid (fluorescent host)− gas (carboxylic acid vapor) contact, as described by the authors.…”
Section: Fluorescent/colorimetric Sensors Based On Phenanthro[910-d]i...mentioning
confidence: 99%